FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI EMPIRIS PADA SATKER BALAI BESAR BMKG WILAYAH III DENPASAR-BALI) - Santha Julia Sardi; H. Ahmad Rifa’i; L. Hamdani Husnan (InFestasi, 2016)
This study aims to examine empirically the effect of the influence of Clarity Target Budget, Internal Control Systems, Human Resources and Government Accounting Standards on Financial Statement Quality and Accountability Government Performance. The population was 366 respondents KPA / PPK and treasurer at 183 work units BMKG. The number of samples is determined by purposive sampling technique, resulting in a sample of 94 respondents consisting of 47 units working under the coordination of the Center for BMKG Region III Denpasar-Bali. Collecting data using primary data by distributing questionnaires. Data analysis tool used is Partial Least Square (PLS). Tests on the research done by using second order confirmatory factor analysis. The findings of this study indicate that: (1) Quality of Financial Statements significantly affected by Goal Clarity Budget and Government Accounting Standards, but was not significantly affected by SPI and natural resources; (2) Accountability of Government Performance is significantly affected by SPI and SAP, but was not significantly affected by Goal Clarity Budget and Human Resources; (3) Quality of Financial Statements significantly influence the Government Performance Accountability. The implications of this study may be useful as consideration for decision makers in improving the quality of financial statements and Accountability Government Performance as a form of state financial management.